(untitled) (Filološke studije, 2019)
In the article is considered the development of one of the most productive and quantitatively predominant genres in Slovene literature – the historical novel – from its origin in the XIXth century till its golden age between the two World wars. The author has made an attempt to retrace its genealogy, to find necessary perquisites of its emergence and to determine its role in the national cultural life. Genesis of genre gives an opportunity to mark some distinguishing features of genre poetics out and to estimate its valuable contribution not only to the national literature but also to the European ones.